Detection of plaque structure and composition using OCT combined with two‐photon luminescence (TPL) imaging. Issue 6 (27th May 2015) - Wang, Tianyi; McElroy, Austin; Halaney, David; Vela, Deborah; Fung, Edmund; Hossain, Shafat; Phipps, Jennifer; Wang, Bingqing; Yin, Biwei; Feldman, Marc D.; Milner, Thomas E.
Abstract : Background and Objectives: Atherosclerosis and plaque rupture leads to myocardial infarction and stroke. A novel hybrid optical coherence tomography (OCT) and two‐photon luminescence (TPL) fiber‐based imaging system was developed to characterize tissue constituents in the context of plaque morphology. Study Design/Materials and Methods: Ex vivo coronary arteries (34 regions of interest) from three human hearts with atherosclerotic plaques were examined by OCT–TPL imaging. Histological sections (4 μm in thickness) were stained with Oil Red O for lipid, Von Kossa for calcium, and Verhoeff–Masson Tri‐Elastic for collagen/elastin fibers and compared with imaging results. Results: Biochemical components in plaques including lipid, oxidized‐LDL, and calcium, as well as a non‐tissue component (metal) are distinguished by multi‐channel TPL images with statistical significance ( P < 0.001). TPL imaging provides complementary optical contrast to OCT (two‐photon absorption/emission vs scattering). Merged OCT–TPL images demonstrate the distribution of lipid deposits in registration with detailed plaque surface profile. Conclusions: Results suggest that multi‐channel TPL imaging can effectively identify lipid sub‐types and different plaque components. Furthermore, fiber‐based hybrid OCT–TPL imaging simultaneously detects plaque structure and composition, improving the efficacy of vulnerable plaque detection and characterization. Lasers Surg. Med. 47:485–494, 2015. © 2015 Wiley Periodicals, Inc.